Catch-up vaccination campaign in children between 6 and 8 years old during COVID-19 pandemic: The experience in a COVID hub in Milan, Italy. Issue 26 (9th June 2022) - Mancarella, Matteo; Natarelli, Federica; Bertolini, Caterina; Zagari, Antonino; Enrica Bettinelli, Maria; Castaldi, Silvana
Highlights: The COVID-19 pandemic has resulted in a slowdown in routine childhood immunizations. Planning of a four days catch-up vaccination campaign during COVID-19 pandemic respecting the standards required to prevent possible contagion and to guarantee interpersonal distancing. The catch-up vaccination campaign has allowed increasing the vaccination coverages of children aged between 6 and 8 years in Milan. Abstract: Background: COVID-19 has led to disruption in routine immunization programs around the world. Effective strategies need to be developed to address the decline in vaccine coverage to avoid preventable disease outbreaks. Our study reports a 4-days campaign for the catching-up of missed vaccinations in children aged between 6 and 8 years, in Milan, Italy. Methods: The catch-up vaccination campaign (21st-24th of September 2021) involved children born in 2013, 2014 and 2015. These cohorts, if not already immunized, received the fourth dose of the Diphtheria-Tetanus-acellular Pertussis and Poliomyelitis vaccination (DTaPP4), the second dose of the Measles-Mumps and Rubella vaccination (MMR2) and Chickenpox, according to the Italian vaccine schedule. Results: 3, 943 letters were sent to children with a missing vaccination. 1, 315 children, 33% of expected, were vaccinated during the campaign. The 2015 cohort was the one that benefited most from the initiative, 955 children were vaccinated for a total of 1, 864 doses administered. This has led to a significant increase of 20.0 percentage points (p.p.) in vaccination coverages for the fourth dose of DTaPP and the second dose of MMR. 214 children for the 2014 cohort and 146 for the 2013 cohort were vaccinated during the following days, these cohorts have been already called previously therefore the participation in the campaign and consequently the increase in vaccination coverages were less substantial. Conclusions: This experience has demonstrated that a mass vaccination campaign could be a useful tool in catch-up strategies, even during the pandemic. It should be part of a bigger immunization program strategy that also includes efforts to simultaneously strengthen routine immunization services. With the appropriate organizational improvements, this initiative could pave the way for future successful campaigns involving different age groups and vaccinations.